One step forward, two steps back: Tensions between malaria elimination and improved malaria surveillance in the Solomon Islands - Sebastian Kevany (AIMS Press, 2020)
The Solomon Islands experienced, between 2010, an apparent meteoric fall in the level of malaria incidence and prevalence [1]. Thanks ostensibly to the efforts of bilateral and multilateral partners and donors, annual parasite incidence (API) fell from 70 to 40 per 1,000 population. With such dramatic progress, international efforts were hailed as dramatic successes and showcased as progress towards malaria elimination and eradication, Yet, paradoxically, the true caseload of malaria in the Solomon Islands has revealed a situation that calls for more, rather than less, support.